(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2025)
We present the results of a research whose objective is: to carry out a phenomenological hermeneutic study of female selfleadership, seen from the empowerment of seven Venezuelan migrant women living in the United States, Mexico and Costa Rica, born in the 20th century between the 1930s and the 1990s. Regarding the hermeneutic horizon, these women exercise selfleadership from the use of gestalt intelligence in challenging sociohistorical contexts.In the methodological approach, the triangulation of methods was used to adapt to the specificities of the versions of the interviewees as units of analysis to achieve an understanding of the action of human life from the experience of these migrants.It is concluded that the way emotions are managed makes a difference in the resilience and empowerment of these women without ageism.